Barycentric Rational Collocation Method for Nonlinear Heat Conduction Equation - Jin Li (Journal of Applied Mathematics)
Nonlinear heat equation solved by the barycentric rational collocation method (BRCM) is presented. Direct linearization method and Newton linearization method are presented to transform the nonlinear heat conduction equation into linear equations. The matrix form of nonlinear heat conduction equation is also obtained. Several numerical examples are provided to valid our schemes.